2015
DOI: 10.1089/tmj.2014.0092
|View full text |Cite
|
Sign up to set email alerts
|

How the Awareness of u-Healthcare Service and Health Conditions Affect Healthy Lifestyle: An Empirical Analysis Based on a u-Healthcare Service Experience

Abstract: Objective: The objectives of this study are (1) to establish a ubiquitous healthcare (u-healthcare) center for those who wish to use u-healthcare, allowing them to experience the service, and (2) to evaluate the users' awareness and expectations of the service based on their overall assessment. Materials and Methods: To establish the u-healthcare center, a kiosk, devices for health checkup, a body-type examination system, and a physical fitness assessment system were installed. Also, a u-healthcare Web site wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In 2017, Beaulieu-Jones and Moore [16] examined electronic health records (EHRs), which are a source of important data for patient status but have a lot of missing data. In this paper, imputation of missing information using deeply learned autoencoders in the Pooled Resource Open-Access ALS Clinical Trials Database (PRO-ACT) showed strong performance on estimation accuracy and contributed as the most powerful predictor of disease progression [17]. In 2019, Azimi et al studied remote health status monitoring used to track patients and provide early detection of disease and preventive care.…”
Section: Related Workmentioning
confidence: 99%
“…In 2017, Beaulieu-Jones and Moore [16] examined electronic health records (EHRs), which are a source of important data for patient status but have a lot of missing data. In this paper, imputation of missing information using deeply learned autoencoders in the Pooled Resource Open-Access ALS Clinical Trials Database (PRO-ACT) showed strong performance on estimation accuracy and contributed as the most powerful predictor of disease progression [17]. In 2019, Azimi et al studied remote health status monitoring used to track patients and provide early detection of disease and preventive care.…”
Section: Related Workmentioning
confidence: 99%
“…In some cases the projects focus on remote monitoring and self-management of diseases such as CVD and COPD, offering solutions to patients that allow them to avoid the need to travel to the hospital for a revision, among other benefits [4] [5]. Other projects put the focus in promoting healthy behaviors in individuals, without health problems, with a more preventive character [6].…”
Section: Related Workmentioning
confidence: 99%
“…This type of data can be obtained from sensors in our architecture and self-monitoring and its tracing facilitate the introduction of changes in lifestyle and purchasing habits [6].…”
Section: A Prehypertensionmentioning
confidence: 99%
“…More than 70% of the surveyed participants indicated their interest in using U-Healthcare services or the Internet as a means of obtaining materials that could provide them with individualized health information [ 15 ]. In another survey, researchers found that only 25.4% of surveyed participants were aware of U-Healthcare services; however, after the surveyed participants used U-Healthcare services, 96.4% found the service helpful for managing their health [ 16 ]. Another study in South Korea analyzed patients with one or more indicators of metabolic syndrome and had the patients use a U-Healthcare service.…”
Section: Introductionmentioning
confidence: 99%